The Capability of Pronouncing French Phonemes by Students of English Department, Udayana University - Indrawati, Ni Luh Ketut Mas; savitri, weddha; Aryani, Agung Istri (Lingual Journal of Language and Culture, 2018)
This study aims at investigating the ability of the pronunciation of French phonemes by students of English Department, Faculty of Culture, Udayana University. It also intends to analyse the way they articulated the phonemes and identified factors affecting their pronunctiation. This research is very interesting to do considering that the correct pronunciation of a phoneme or sound of a Foreign Language is one of the important points that must be mastered by the learners. The French sound system which is different from Indonesian and English certainly becomes one of the obstacles for students besides their lack of knowledge about the French phonemes. It is important to know which phonemes they have been able to pronounce and which are still difficult for them, so that inovations in teaching French can be made, especially in enhancing students' ability in pronouncing sounds which are considered difficult in French.                Forty students of English Department who chose French as their elective subject were taken as the population of this study. The data were taken by applying observation method using quesionares, recording, and note taking techniqes. The data were descriptive-qualitatively analysed by applying the theory of phonology.   Keywords : capability, pronunciation, phonemes, French.